Character Education on Family Environment in Indonesia - Priyanto, Priyanto (International Conference of Moslem Society, 2018)
This research aimed to determine the process of character education on family environment in Indonesia, both in single and two parents’ families. This research was a qualitative research. The results of the interviews and observations were noted in field notes. The data were analyzed using inductive approach with interactive models. Meanwhile, the data validity was achieved using the technique of data source triangulation and member checking. The results of this study presented that the family’s view about character education was influenced by the expectations of parents on their children. The encouraged character values included honesty, religiosity, democracy, communication, discipline, hard work, responsibility, humility, self-reliance, and empathy. Parents built characters to their children through good parenting, exemplifying behavior and habits, providing explanation for their actions, implementing a high but realistic standard for the children, and involving children in decision-making. The results of character education within family showed that the children who grew up in two parents’ family got more affection than those who grew up in single parent family. The number of children with problems and self-reliance was few, but the children were more obedient.